Variation of some heavy metal concentrations due to traffic intensity in Prunus cerasifera leaves, seeds and branches - Ozer Genç Cigdem; Ozturk Ayse; Akarsu Hatice; Abacioglu Ezgi (GSC Online Press, 2019)
This study aimed that the increasing population and the number of vehicles in the cities have brought air pollution. It has become one of the most important problems of the modern age. Many pollutants emerge from city roads due to exhaust gases, car wheels, vehicles and vehicle wear, and these sources of pollution are affecting the development and health of living things in their environment. Among these pollution factors, heavy metals have a huge important role of air pollution. The heavy metals tend to bioaccumulate and some have toxic effects even at very low concentrations. Therefore, monitoring of the change in heavy metal concentration is extremely important. Plants are used as a biomonitor for determining heavy metal pollution. In this study, it was tried to determine the possibilities of using Prunus cerasifera as biomonitor which is frequently used in landscape studies. So concentrations of Ba, Al, Ca, Fe, K and Mg elements were determined by analyzing Prunus cerasifera leaves, seeds and branches collected from some areas including no traffic, mid-intensity, intense traffic. As a result of the study, it was determined that the elements other than K were significantly changed at confidence level of least 95% on the basis of organelles. When the changes of the elements on the basis of organelle depending on traffic density were examined, it was found that the concentrations of Ca in leaf, Ba and K in seed, Ba, Fe and Mg in branch increased depending on traffic density.
Keywords: Prunus cerasifera; Leaves seeds; Branches; Heavy metal; Traffic; Biomonitor; 13. Climate action; 11. Sustainability; 15. Life on land; 6. Clean water